The chemical degumming process and effect on the composition, structure and properties of Apocynum venetum. Issue 1 (January 2020) - Lou, Jianting; Yao, Lan; Qiu, Yiping; Lin, Huoyue; Kuang, Ye; Qi, Sihao
Apocynum venetum (AV) is a kind of rare wild plant with a strong capability for survival in the world and is named the "the king of wild fiber." As AV bast fibers have defects due to natural and operational interventions, it is difficult to degum them thoroughly. In this study, chemical degumming was applied to obtain degummed fibers for further treatment. The details of degumming were provided and the necessary characterizations of the degummed fibers were tested and analyzed. The average length of AV fiber was 29.68 mm, concentrated in the range of 10–50 mm, which was suitable for blending with cotton, wool, etc. In addition, the fineness of AV fibers was 4673.25 Nm. From the results of color data, AV fibers were reddish yellow. Scanning electron microscopy results showed that the degummed single AV fiber had a certain number of nodes distributing randomly on the surface. The Fourier transform infrared spectrum showed that the peaks associating with the pectin, hemicellulose and lignin decreased significantly, indicating the effectiveness of the chemical degumming. In addition, the AV bast fibers and AV fibers had strong abilities in absorbing water moisture with regains of 11.56% and 8.7%, respectively. For the mechanical properties, the degummed AV fibers had a similar modulus of 401.56 cN/dtex to that of ramie fibers. The X-ray diffraction results indicated that after degumming, the crystalline structure was more obvious. These results provided the necessary basis for studying the structures of AV bast and degummed fibers and provided preparation for further fiber mat reinforced composites.